Role of Securin, Separase and Cohesins in female meiosis and polar body formation in Drosophila. - Guo, Z.; Batiha, O.; Bourouh, M.; Fifield, E.; Swan, A. (Journal of Cell Science, 2016)
Chromosome segregation in meiosis is controlled by a conserved pathway that culminates in Separase-mediated cleavage of the ?-kleisin Rec8, leading to dissolution of cohesin rings. Drosophila has no gene encoding Rec8, and the absence of a known Separase target raises the question of whether Separase and its regulator Securin (Pim in Drosophila) are important in Drosophila meiosis. Here, we investigate the role of Securin, Separase and the cohesin complex in female meiosis using fluorescence in situ hybridization against centromeric and arm-specific sequences to monitor cohesion. We show that Securin destruction and Separase activity are required for timely release of arm cohesion in anaphase I and centromere-proximal cohesion in anaphase II. They are also required for release of arm cohesion on polar body chromosomes. Cohesion on polar body chromosomes depends on the cohesin components SMC3 and the mitotic ?-kleisin Rad21 (also called Vtd in Drosophila). We provide cytological evidence that SMC3 is required for arm cohesion in female meiosis, whereas Rad21, in agreement with recent findings, is not. We conclude that in Drosophila meiosis, cohesion is regulated by a conserved Securin-Separase pathway that targets a diverged Separase target, possibly within the cohesin complex.